2007
DOI: 10.1007/s00464-006-9180-x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and patient satisfaction after laparoscopic antireflux surgery using the QOLARS questionnaire

Abstract: The findings show that QOLARS is a sensitive tool for assessing surgical outcome after laparoscopic antireflux surgery. The quality-of-life response closely follows the clinical outcome of surgical treatment, reflecting its side effects as well. This study suggests that a generic quality-of-life scale can preoperatively identify patients with GERD who are likely to be dissatisfied with antireflux surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
1
11
0
1
Order By: Relevance
“…Furthermore, the patients who obtained symptom relief and good QoL values continued to do so. These kinetics are consistent with the literature on adult patients [8,21,22].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Furthermore, the patients who obtained symptom relief and good QoL values continued to do so. These kinetics are consistent with the literature on adult patients [8,21,22].…”
Section: Discussionsupporting
confidence: 81%
“…It is suggested that a low preoperative QoL may predict a poor functional outcome [22,24]. It is known that for dystrophic and neurologically impaired children and their parents, lower preoperative functional and QoL scores throughout all dimensions [25] may correspond with a poorer functional outcome [2,4] and a higher recurrence rate [19] than for normal children [18].…”
Section: Discussionmentioning
confidence: 99%
“…Improvement in short term results in quality of life after laparoscopic fundoplicaton has been widely reported (31)(32)(33). To the authors' knowledge, our prospective study comparing long-term quality of life results in patients undergoing either traditional or robotic fundoplication is the first desription in the existing literature.…”
Section: Discussionmentioning
confidence: 88%
“…Following laparoscopic antireflux surgery, dysphagia has been reported to significantly improve from preoperative values [47,188,197,198,[200][201][202][203][204] (level II-III). Despite reports of improved dysphagia following surgery, postoperative dysphagia remains a significant problem, with reported reoperation rates ranging from 1.8 to 10.8% [33,34,38,39,143,196,[205][206][207] (level I-III) and endoscopic dilatation rates ranging from 0 to 25% [34,121,143,145,189,195,196,[208][209][210][211][212][213] (level I-III). Although perioperative and early postoperative dysphagia have been reported as high as 76% [191] (level II), the majority of studies show early and mid dysphagia rates, up to 1 year postoperatively, of less than 20% [33,34,38,39,44,47,120,122,189,191,192,195,196,199,200,…”
Section: Discussionmentioning
confidence: 99%